Integration of General Knowledge and Religion Policy for the Emergence of Integrated Islamic Schools (International Journal of Education and Literature, 2025)
The dichotomy between general sciences and religious sciences has become a fundamental issue in modern educational systems, resulting in the emergence of a generation fragmented in knowledge and values. In the context of Indonesian Muslim society, the emergence of Integrated Islamic Schools (Sekolah Islam Terpadu/SIT) serves as a response to concerns over a secular-oriented education system that fails to address spiritual dimensions and holistic character development. This study aims to analyze how the integration of general and religious knowledge serves both as a paradigmatic foundation and a policy driver behind the rise of SIT as an alternative educational model. The research employs a qualitative approach using the Systematic Literature Review (SLR) method, involving an in-depth analysis of scholarly literature, policy documents, and relevant research findings. The results reveal that knowledge integration within SIT goes beyond curriculum unification; it involves an epistemological reconstruction of education that unites cognitive and spiritual dimensions within a tawhidic (monotheistic) framework. National education policy provides a legal space for the development of SIT, while the strategic role of SIT is evident in its capacity to nurture students who are academically competent and morally grounded. This study highlights the importance of strengthening policy and institutional capacity to ensure the sustainability of an integrative and contextually responsive Islamic education system.